2020
DOI: 10.1002/bip.23406
|View full text |Cite
|
Sign up to set email alerts
|

Anion‐regulated binding selectivity of Cr(III) in collagen

Abstract: We present a mechanism for the selectivity of covalent/electrostatic binding of the Cr(III) ion to collagen, mediated by the kosmotropicity of the anions. Although a change in the long-range ordered structure of collagen is observed after covalent binding (Cr(III)-OOC) in the presence of SO 4 2− at pH 4.5, the ν sym (COO −) band remains intense, suggesting a relatively lower propensity for the Cr(III) to bind covalently instead of electrostatically through Cr(H 2 O) 6 3+. Replacing SO 4 2− with Cl − reduces th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…When treated with chromium( iii ) sulfate (CS) (COL-Cr), the known changes in peak intensities and positions are confirmed. 35,36 The 3 rd order peak diminishes while the others increase relatively. The peaks also see shifts towards higher q values indicating a smaller D-period between collagen molecules, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When treated with chromium( iii ) sulfate (CS) (COL-Cr), the known changes in peak intensities and positions are confirmed. 35,36 The 3 rd order peak diminishes while the others increase relatively. The peaks also see shifts towards higher q values indicating a smaller D-period between collagen molecules, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SERS peaks of collagen are observed at [Coll] final = 25 μg/mL at 3357, 2934 (ν­(CH 3 ); ν­(CH 2 )), 2877 (ν s (CH 3 )), 1731 (ν­(CO), in COOH of Asp or Glu), 1670 (Amide I (ν­(CO), β-sheet); ν as (COO – )), 1636 (Amide I (ν­(CO), 3 10 -helix); ν as (COO – )), 1444 (δ­(CH 3 ); δ­(CH 2 )), 1410 (ν s (COO – )), 1384 (ν s (COO – )),1321 (τ­(CH 3 ); τ­(CH 2 )), 1264 (Amide III, δ­(N–H)), 1244 (Amide III, ν­(C–N)), 1027 (ν 18a , Phe or Tyr), 934 (ν­(C–C), backbone), and 854 cm –1 (ν­(C–C), Pro ring) (Table S5). The enhanced ν s (COO – ) peak at 1410 cm –1 could indicate the formation of direct coordinative binding of collagen with Ag atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic efficacy of catalysts is improved by enhancing active sites, decreasing particle size [ 42 , 43 ], and enhancing the dispersity of active particles [ 44 ]. The active metals (Ag, Cr (III), Fe (III), and Zr (IV) [ 45 , 46 ]) form biological coupling reactions with the hydroxyl, carboxyl, amine, and other functional groups in the protein chains [ 47 , 48 ] and fix them on the collagen fibers. Bi Shi’s research group reported that Fe(III) ions were fixed on collagen fibers to prepare a renewable heterogeneous photocatalytic catalyst for the degradation of Malachite Green MG and Orange II [ 49 , 50 , 51 ].…”
Section: The Structural Advantages Of Collagen and Silk Fibroin For C...mentioning
confidence: 99%